A Voluntary End of Earth. Melancholia and Jean Améry - Sebastian Thede (Current Objectives of Postgraduate American Studies)
This essay interrogates the semantics of finality in Lars von Trier’s Melancholia “(2011), in the light of Austrian theorist Jean Améry’s 1976 study On Suicide. A Discourse on Voluntary Death“. I suggest an apsychological reading of Melancholia“, to unwrap its narrative and philosophical reflections on a desire for the end of earth.